Pengaruh Lama Kerja terhadap Tingkat Organizational Citizenship Behavior (OCB) Perawat Suku Bugis di Instalasi Rawat Inap Rumah Sakit Labuang Baji - Andi Indahwaty Sidin; Yahya Thamrin; Rifa’ah Mahmudah (Media Kesehatan Masyarakat Indonesia, 2019)
Bugis tribes is one of the most widely tribes spread in Indonesia known to have high enthusiasm, likes adventureand wandering.Their cultural value may affect to their performance in organization.This study aim was to analyzethe influence length of work employment on organizational citizenship behavior of bugineese nurse in the inpatientunit at Labuang Baji Hospital. This research is a quantitative research. The design used was analytic observationalwith a cross-sectional study approach. A sample of 98 nurses were selected by purposive sampling technique withthe Bugis tribe criteria. Data were analyzed using multiple linear regression tests. The results of the study showedthat all bugineese nurses at inpatient unit at Labuang Baji Hospital had a high OCB level. The results of the linearregression test between the length of employment and OCB showed that there was no effect between length ofemployment and OCB, with value of p = 0.203> 0.005. It was concluded that nurses had a high level of OCB, althoughwith different length of work, this was because the bugineese nurses had reflected the cultural value of siri ‘na pesse inthe form of matinulu (hard work), getteng (firm) and marenreng perru (loyal) when provided services in the hospital.